Incidence and risk factors for hepatic sinusoidal obstruction syndrome after allogeneic hematopoietic stem cell transplantation: A retrospective multicenter study of Turkish hematology research and education group (ThREG). (August 2020) - Soyer, Nur; Gunduz, Mehmet; Tekgunduz, Emre; Deveci, Burak; Ozdogu, Hakan; Sahin, Handan Haydaroglu; Turak, Esra Ermis; Okay, Mufide; Kuku, Irfan; Hindilerden, Ipek Yonal; Topcuoglu, Pervin; Altuntas, Fevzi; et al.
Abstract: Hepatic sinusoidal obstruction syndrome (HSOS) is a potentially life-threatening complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT). We retrospectively evaluated the incidence, risk factors, treatment and survival for HSOS after allo-HSCT in Turkey. We also reported our experience of defibrotide (DF) for HSOS prophylaxis in high-risk (HR) patients. Across Turkey, 1153 patients from 10 centers were enrolled in the study. We evaluated the medical records of patients who were treated with allo-SCT between January 2012 and December 2015. The study included 1153 patients (687 males/466 females) with median age of 38 (15−71) years. The incidence of HSOS was 7.5 % (n = 86). The incidences of HSOS in the HR/DF+, HR/DF- and standard risk (SR) group were 8%, 66.7 % and 6.2 %, respectively. The rate of HSOS development was not statistically different between HR/DF + and SR group (p = 0.237). HSOS prophylaxis (defibrotide) was significantly decreased HSOS-related mortality (p = 0.004). The incidence of HSOS was found similar to literature in this large Turkish cohort. Defibrotide prophylaxis appears to be associated with low incidence of HSOS development and reduced HSOS-related mortality. Although these results are promising, future studies are needed to support the efficacy of defibrotide prophylaxis in patients with risk of HSOS.